THE ROLE OF EXPERIENCE AND SERVICE QUALITY ON TRANSJAKARTA USERS LOYALTY - Sangkoyo, Adhitya Bayu Candra; Adiwijaya, Karto (Fakultas Ekonomi dan Bisnis, UNTAN, 2024)
The high growth rate of vehicles and the still low interest in using public transportation, especially in Jakarta, has led to an increase in urban issues such as traffic congestion and air pollution. The government has provided several modes of public transportation and has implemented several policies to reduce these issues however until now there has been no significant growth in the usage of public transportation. This study aims to test experience and service quality on mediating variable such as satisfaction, perceived value and memories that leading to how customer decide to repurchase the service or recommend it through word-of-mouth. This research uses PLS-SEM to conduct quantitative research and collected 369 respondents online through whatsapp community groups that target Transjakarta passengers. This research found experience marketing is the strongest construct to influence other mediating constructs. This findings contributes the influence of experience in public transportation context and also to Transjakarta management, practitioners, consultants or even the government in the realm of public transportation.JEL: M31.